A novel approach to determine post mortem interval using neutron radiography. (June 2015) - Bilheux, Hassina Z.; Cekanova, Maria; Vass, Arpad A.; Nichols, Trent L.; Bilheux, Jean C.; Donnell, Robert L.; Finochiarro, Vincenzo
Highlights: Post-mortem interval (PMI) was determined using neutron radiography of canine tissues. Tissues and cadavers were decayed under controlled (lab-setting) and uncontrolled (environmental) conditions. PMI was calculated from the neutron transmission of tissues as a function of time. Natural logarithmic fit was used to estimate PMI. Abstract: One of the most difficult challenges in forensic research is to objectively determine the post-mortem interval (PMI). The accuracy of PMI is critical for determining the timeline of events surrounding a death. Most PMI techniques rely on gross morphological changes of cadavers that are highly sensitive to taphonomic factors. Recent studies have demonstrated that even exhumed individuals exposed to the same environmental conditions with similar PMIs can present different stages of decomposition. After death, tissue undergoes sequential changes consisting of organic and inorganic phase variations, as well as a gradual reduction of tissue water content. Hydrogen (H) is the primary contributor to neutron radiography (NR) contrast in biological specimens because (1) it is the most abundant element in biological tissues and (2) its nucleus scatters thermal and cold neutrons more strongly than any other atomic nucleus. These contrast differences can be advantageous in a forensic context to determine small changes in hydrogen concentrations. Neutron radiography of decaying canine tissues was performed to evaluate the PMI by measuring the changes in H content. In this study, dog cadavers were used as a model for human cadavers. Canine tissues and cadavers were exposed to controlled (laboratory settings, at the University of Tennessee, College of Veterinary Medicine) and uncontrolled (University of Tennessee Anthropology Research Facility) environmental conditions, respectively. Neutron radiographs were supplemented with photographs and histology data to assess the decompositional stages of cadavers. Results demonstrated that the increase in neutron transmission likely corresponded to a decrease in hydrogen content in the tissue, which was correlated with the decay time of the tissue. Tissues depleted in hydrogen were brighter in the neutron transmission radiographs of skeletal muscles, lung, and bone, under controlled conditions. Over a period of 10 days, changes in neutron transmission through lung and muscle were found to be higher than bone by 8.3%, 7.0%, and 2.0%, respectively. Results measured during uncontrolled conditions were more difficult to assess and further studies are necessary. In conclusion, neutron radiography may be used to detect changes in hydrogen abundance that can be correlated with the post-mortem interval.